Learners’ attitudes towards engaging in online communication activities / Goh Chin Shuang and Tan Teow Ghee and Turisiana Ahmad Buhari - Goh, Chin Shuang; Tan, Teow Ghee; Ahmad Buhari, Turisiana (UiTM Press, 2016)
Blended learning has been implemented in Universiti Teknologi MARA (UiTM) since 2009. However, there is still no known study on the attitudes of learners who engage in online communication activities in the study of Mandarin. Thus, this study was carried out to investigate the attitudes of learners who engage in online communication activities while studying Mandarin. The sample for this study comprised 201 students from eight classes of seven faculties at UiTM, Shah Alam. The data were collected via observations of the sample’s online communication activities in the i-Learn portal for one semester. Throughout the semester, the researchers monitored the sample’s activities and the results revealed that most of the sample showed a positive attitude towards online communication activities despite certain challenges faced by lecturers in online communication activities. The findings of this research will serve as a helpful reference to guide the teaching and learning of Mandarin among non-native or third language learners to actively engage them in online communication activities that create.